(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines primary errors that occur in the direct translation of phraseological units and methods for their prevention. The study suggests effective translation strategies considering cultural and linguistic characteristics of idiomatic expressions.